High transparent glass of germanate-borate-tellurite modified by different concentration of bismuth oxide for optical and radiation shielding applications - Mahmoud, K.A.; Sayyed, M.I.; Mhareb, M.H.A.; Kadhim, Abed Jawad; Kaky, Kawa M.; Hamad, M. Kh; Baki, S.O. (Elsevier, 2024)
The current investigation studied one of the high-density heavy metal oxides (Bi2O3) having density = 8.9 g/cm³, which was utilized to improve structural and optical features of the B2O3–TeO2-GeO2-MgO glass system. Three high transparent glasses with a chemical formula of 35B2O3–20TeO2-10GeO2-35MgO-xBi2O3 (x = 5, 10, and 15 mol %) were fabricated by melting at 1100 °C for 20 min and annealing at 400 °C for 5 h. X-ray diffraction measurements for the Bi5 sample, containing 5 mol % Bi2O3, were obtained at the range of 10°–80° to inspect the structural characteristics of the made glasses. Optical absorption was employed and recorded for Bi5, Bi10, and Bi15 samples at wavelength range 300–1000 nm to examine the optical properties, including optical band gap. Using Makishima and Mackenzie methods, the mechanical features of the glass samples were assessed. Nuclear library ENDF/B-VI.8 is coupled to the MCNP-5 code and is used to study and simulate the prepared Bi glass sample shielding parameters. The ionizing absorption properties for the prepared Bi5, Bi10, and Bi15 samples were found to be changed because of many circumstances like the photon energy (Eγ, MeV), and chemical compositions (Bi2O3 content (mol. %). The increased layer thickness of glass between 25 and 200 mm enhances the RPE values at 0.6 MeV over the range of 16.31–50.93 % (Bi5 glass sample), 18.68–56.26 % (Bi10 glass sample), and 20.80–60.66 % (Bi15 glass sample). © 2024